The Sovereignty of Joy : Nietzsche's Vision of Grand Politics - McIntyre, Alex, 1950- (Book collections on Project MUSE., 1997)
"In the Sovereignty of Joy: Nietzsche's Vision of Grand Politics, Alex McIntyre suggests that a sense of tragic joy is the legislating experience at the heart of Nietzsche's philosophy. A Dionysian exuberance animates all of Nietzsche's central ideas - will to power, self-mastery, the Overman, amor fati, eternal return - and especially his 'grand politics, ' which McIntyre argues is the political elaboration of the sovereignty of joy." "This study interprets Nietzsche's conception of tragic joy as the affirmation of the fullness of becoming at every moment, an affirmation which overcomes revenge and nihilism by embracing suffering and loss. As the embodiment of tragic joy, the Overman represents a new form of philosophical statesmanship that cannot be reduced to either a politics of domination or an idealistic utopianism, for such an interpretation ignores the 'atopian' nature of Nietzsche's grand politics. McIntyre characterizes 'atopia' as the double position of the Nietzschean philosopher at both the centre and the periphery of a political culture through the revaluation of all values."--Jacket.